Dynamics of apex and leaf development in barley as affected by PPD-H1 alleles in two contrasting PHYC backgrounds under short or long photoperiod - Parrado, Jorge D.; Savin, Roxana; Slafer, Gustavo A. (Frontiers in Plant Science, 2024)
Barley development from seedling to flowering involves both external and internal changes, the latter requiring microscopic observation. Internal changes allow for the classification of preflowering development into three phases: vegetative, early reproductive, and late reproductive. Genetic and environmental factors influence the duration of these phases, impacting grain yield. Photoperiod-sensitivity genes PPD-H1 play a major role in flowering time, affecting adaptation; however, the effect might also be direct (beyond affecting phenology). In this paper, we aimed to assess how PPD-H1 alleles affect barley development, including the progression of growth phases, leaf emergence, tillering dynamics, and spikelet development. Two experiments (field and controlled conditions) were conducted with a factorial combination of (i) four near-isogenic lines (NILs) for PPD-H1 alleles (ppd-H1 or Ppd-H1) under two contrasting PHYC genetic backgrounds (PhyC-l and PhyC-e) and (ii) two photoperiod conditions (short and long days). As expected, longer photoperiods led to a shorter growth cycle. All subphases of time to flowering, final leaf number, and phyllochron were affected by photoperiod. The effects of PPD-H1 on flowering time depended on the PHYC genetic backgrounds and photoperiod conditions. PPD-H1 effects on flowering time were associated with leaf number and phyllochron; the interplay between leaf number and phyllochron affected mainly the late reproductive phase. We also found that although PPD-H1 did not affect the phyllochron of the first six leaves, the phyllochron of leaves appearing later, when grown under a short photoperiod, was consistently increased in lines carrying the ppd-H1 allele. Tillering dynamics exhibited variability, but PPD-H1 did not affect the final spike number under a 24-h photoperiod.